Pancasila Perspektif Mohammad Hatta sebagai Dasar Pendidikan Islam di Indonesia - Fuady, Ahmad Syauqi (Koordinatorat Perguruan Tinggi Keagamaan Islam Swasta Wilayah IV Surabaya, 2019)
This article aims to find out how Mohammad Hatta's interpretation of Pancasila is. And how these values ​​become the basis of the implementation of Islamic education in Indonesia. Mohammad Hatta was a Muslim nationalist who was involved in the birth of Pancasila. The Islamic style of Mohammad Hatta is oriented towards substance rather than formality and symbols such as salt rather than lipstick. As a devout Muslim and nationalist, his interpretation of Pancasila was accepted by different political groups. Pancasila, according to Hatta, contains two main fundamentals, namely the moral fundamentals of religious ethics (1st principle) and political fundamentals (2nd to 5th precepts). The Precepts of Godhead become the basis for leading the other precepts. The existence of the One Precepts of Godhead as the first precepts causes the five precepts to bind to each other and creates a harmonious pair between the five precepts in Pancasila. Pancasila for Mohammad Hatta is a guideline for realizing happiness, prosperity, peace and independence in a perfectly sovereign Indonesian society and legal state. The practice of implementing Islamic Education in Indonesia should make these four things as things that need to be realized. The basic values ​​of the Pancasila perspective of Mohammad Hatta to be used as the basis for the implementation of Islamic education in Indonesia: Divine values, human values, unity values, social values, and justice values